Pengaruh Pertumbuhan Penduduk terhadap Perkembangan Permukiman di Kecamatan Koto Tangah Tahun 2012-2022 - Fitri, Rahmadini Awlya; Afdhal, Afdhal (Lembaga Yasin AlSys, 2024)
Koto Tangah sub-district is one of the largest sub-districts in Padang City, this sub-district has an increase in population from year to year, which has an impact on increasing the area of land use for residential settlements. The type of research is descriptive quantitative using settlement maps in 2012 and 2022 and population data in 2012-2022. The analysis technique used is the geometric calculation method to calculate the population growth rate in 2012-2022, overlaying the 2012-2022 settlement map, nearest neighbor analysis and simple linear regression. The results showed that there was an increase in population during the period. The analysis of population growth and settlement development of Koto Tangah Subdistrict from 2012 to 2022 for a ten-year period showed a stable trend. In 2012-2022 there was a population growth of 1.7% with settlement development increasing by 817.27 Ha. The pattern of settlement development in Koto Tangah Sub-district is a clustered pattern following the road network, with the direction of development more dominant to the East and North. The correlation analysis shows that the relationship between population growth and the development of settlement area is very strong (R = 0.699), indicating a strong positive relationship between the two variables. The coefficient of determination (R Square) of 0.489 reveals that population growth has an influence of 48.9% on the development of settlement area. These results indicate that population growth has a significant influence on settlement development.